PEMBERDAYAAN POTENSI LOKAL MELALUI PROMOSI DIGITAL MAKAM WALIULLAH SIMBAH BUYUT SRAMBI DI TENGGER WETAN - Kartika Hidayati; Ulya Ainur Rofi'ah; Eka Nur hidayatin; Tsalis Fahmi; Moch. Fais Muhtarom; Tining (CV. Kalimasada Group, 2026)
This study explores the process and outcomes of empowering local communities through digital promotion of the sacred site Waliullah Simbah Buyut Srambi in Tengger Wetan Village. Employing the Asset-Based Community Development (ABCD) approach, the project aimed to shift the focus from community deficiencies to existing local assets, such as spiritual heritage, local leaders, youth communities, and the tradition of pilgrimage. The program was conducted in four stages: discovery (asset mapping), dream and design (formulation of digital promotion ideas), implementation (community-based digital content production), and participatory evaluation (reflection and sustainability planning). Through a participatory mentoring process, community members particularly the youth were guided to recognize their strengths, develop promotional strategies aligned with their cultural values, and create various types of digital content such as videos, historical narratives, and social media materials. These activities were carried out not as top-down training, but as inclusive and collaborative learning experiences that strengthened community ownership and creativity. The results of this mentoring program demonstrate that digital promotion can become a transformative tool when rooted in local identity and managed collectively. The community's mindset began to shift from passive consumption to active participation, from dependence to initiative, and from being recipients to becoming producers of cultural narratives. The evaluation phase revealed not only the technical outputs, but also the growth of community confidence, solidarity, and intergenerational collaboration. This experience highlights that ABCD is not merely a development framework, but a philosophy that enables rural communities to build resilience, affirm their spiritual-cultural heritage, and engage with wider audiences through digital means. Ultimately, digital promotion became more than just a means of visibility it evolved into a vehicle for community empowerment and sustainable cultural preservation.